2018
DOI: 10.1080/21678421.2018.1431786
|View full text |Cite
|
Sign up to set email alerts
|

Provision of assistive technology devices among people with ALS in Germany: a platform-case management approach

Abstract: The need for ATD was highly prevalent among ALS patients. Failed or protracted provision posed substantial barriers to ATD procurement. Targeted national strategies and the incorporation of ATD indication criteria in international ALS treatment guidelines are urgently needed to overcome these barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…A few survey studies in different countries have indicated an excessively low access rate of eye-gaze technology because not all individuals with severe disabilities in need of such devices are afforded access to it. For example, a survey study of individuals with ALS in Germany found a rejection rate of 48% by health insurance institutions concerning communication devices such as eye-gaze controlled computer [32]. A survey in the Netherlands on families with a child with Rett syndrome [33] and a study of speech-language therapists in Sweden who support individuals with Rett syndrome [34] show that not all of these individuals have an opportunity to try eye-gaze technology to see if they may benefit from its use.…”
Section: Discussionmentioning
confidence: 99%
“…A few survey studies in different countries have indicated an excessively low access rate of eye-gaze technology because not all individuals with severe disabilities in need of such devices are afforded access to it. For example, a survey study of individuals with ALS in Germany found a rejection rate of 48% by health insurance institutions concerning communication devices such as eye-gaze controlled computer [32]. A survey in the Netherlands on families with a child with Rett syndrome [33] and a study of speech-language therapists in Sweden who support individuals with Rett syndrome [34] show that not all of these individuals have an opportunity to try eye-gaze technology to see if they may benefit from its use.…”
Section: Discussionmentioning
confidence: 99%
“…As Donegan et al ( 88 ) report, the national health service of Italy started providing ETCS for ALS-patients several years ago because of increasing awareness brought by the research, but this is not consistent practice. For Germany, Funke et al ( 89 ) found as a result of a cohort study on a case management program for ALS-patients that only 61% of AAC devices procured by the treating neurologists were finally delivered to the patients, which might be in fact an overestimation for the general population since the study was conducted in specialized ALS centers. The main cause of failed provision with a HT-AAC device was rejection by the health insurance, followed by rejection by the patient and patient's death.…”
Section: Limitations and Pitfalls Of Ht-aac-use And-supplymentioning
confidence: 99%
“…The mean latency of provision was 93 days, a long period of time for people not able to communicate without the device. The authors speculated that especially decisions over expensive assistive devices are guided by financial considerations at the expense of patients' wellbeing ( 89 ).…”
Section: Limitations and Pitfalls Of Ht-aac-use And-supplymentioning
confidence: 99%
See 1 more Smart Citation
“…The internet platform of APST encompassed the service of coordinators specialized in case management, a tailored digital management platform and assessment tools for selfassessment, services, therapy and assistive devices [11]. The patients and their caregivers were granted access to the APST platform through an account.…”
Section: Settingmentioning
confidence: 99%